Evaluation of computed tomography in management of patients with head injury - Reddy, Santosh; Patil, Nagendra R; Megharaj, Priyanka C (Asian Journal of Medical Sciences, 2023)
Background: The primary goal in treating craniocerebral trauma due to any cause is to preserve the patient’s life and remaining neurological function. It has also made the neuroradiologist an indispensable element of the trauma treatment team. The purpose of this study is to evaluate the efficacy of computed tomography (CT) in the diagnosis, treatment, and prognosis of patients with brain trauma. Aims and Objectives: The objectives of this study were to evaluate the efficacy of CT in the diagnosis, treatment, and prognosis of patients with brain trauma. Materials and Methods: The present study was conducted on patients with head injuries who were referred to the Department of Radiodiagnosis over a 2 years. Details were noted down on pro forma either immediately before or after the procedure was carried out, depending on the status of the patient. Few of the patients underwent plain radiography of the skull before conducting the CT scan. Results: In the present study, the most common lesion observed by CT was edema (49%) followed by contusion (48%), whereas least lesion was observed as intraventricular hemorrhage (4%) and intracerebral hemorrhage (8%). In the present study, the patient with low scores (3–5) showed early deterioration as compared to those with higher scores. This could be attributable to the severity of the primary injury. Late deterioration was more common than early deterioration in scores of >8 where mortality within 48 h was virtually nil and the recovery rate was much higher. Conclusion: This simple, affordable, highly successful, and safe imaging modality should be regarded the initial imaging modality of choice in acute head injury, as it serves as the foundation for cornerstone for rapid and effective diagnosis.